Patent portfolios and Patent Assertion Entities: antitrust issues and future perspective under the Unified Patent Court - Cappabianca, Pietro (Revista de Estudios Jurídicos y Criminológicos, 2024)
Protecting research has always been a relevant issue in order to foster innovation, especially in the pharmaceutical field. Intellectual property rights protection plays a main role in the current economy since it allows companies to monetize efforts and investments in research and development through the patent system. However, in the past years antitrust authorities found themselves in front of a tangled question: the strategic use of patents in order to unlawfully prolong the protection time and, by so doing, to exclude competitors from the market. The strategic use of patent portfolios and the rapid growth of Patent Assertion Entities represent a significant antitrust issue which needs to be investigated, especially following the Agreement on unitary patent and Unified Patent Court and the related deep changes in the European patent system in order to verify if such Agreement can be a useful tool against strategic and anti-competitive conducts.